The relationship between the number of stenotic coronary arteries and the gut microbiome in coronary heart disease patients - Yu, Hao; Li, Le; Deng, Yu; Zhang, Guolan; Jiang, Mimi; Huang, He; Li, Cheng; Lv, Zhiyu; Zhou, Yingshun; Liu, Xing (Frontiers in Cellular and Infection Microbiology, 2022)
An increasing number of studies have shown that the gut microbiome plays an important role in the development of coronary heart disease (CHD). However, there are no clear studies on the relationship between the gut microbiome and the number of stenotic coronary arteries. To clarify whether the gut microbiome is associated with the number of stenotic coronary arteries in CHD, we performed the 16S rRNA gene sequencing for the V3-V4 region in the gut microbiota from 9 healthy controls (C) and 36 CHD patients, which including 25 CHD patients with multivessel (MV) lesion and 11 CHD patients with single-vessel (SV) lesion. It showed that the abundance of the genus Escherichia-Shigella was significantly increased in the MV and SV groups compared with C group, while the abundance of the genera Subdoligranulum and Collinsella was significantly decreased. Biomarkers based on three gut microbiotas (Escherichia-Shigella, Subdoligranulum, and Collinsella) and three plasma metabolites(left atrial diameter (LA), low density lipoprotein (LDL), and total bile acids (TBA)) were able to distinguish CHD patients with different numbers of stenotic coronary arteries. Functional prediction of the gut microbiome was performed based on the Kyoto Encyclopedia of Genes and Genomes (KEGG) database. The results showed that the gut microbial function of MV and SV group patients was richer than C group in betaine biosynthesis and unsaturated fatty acid biosynthesis, in the contrast less than C group in sphingolipid metabolism and primary bile acid biosynthesis. In summary, our study showed that the composition and function of the gut microbiome changed significantly from healthy controls to CHD patients with different numbers of coronary lesions.